Organic matter accumulation of the Wufeng-Longmaxi shales in southern Sichuan Basin: Evidence and insight from volcanism. (October 2020) - Tang, Ling; Song, Yan; Jiang, Shu; Jiang, Zhenxue; Li, Zhuo; Yang, Youdong; Li, Xiaohui; Xiao, Lei
Abstract: The Wufeng-Longmaxi Formations (WF-LM Fms) in the Sichuan Basin are sets of graptolite-bearing shale strata containing high-frequency bentonite layers. In order to investigate the influence of volcanism on the organic matter (OM) accumulation in shales, detailed observations of several typical profiles and wells were performed. Also, analyses including total organic carbon (TOC) contents and mineral compositions were conducted on 126 shale and 5 bentonite core samples. Major and trace element analyses were conducted on the selected 25 shale and 5 bentonite samples in the WF-LM Fms of well Lu-A. Results show that WF and LM1-4 members are the bentonites concentrated sections, while LM5-6 are the bentonites relatively concentrated sections and no bentonite is found in LM7-9 members. The high potassium (K) content of bentonites have the typical characteristics of intermediate-acid calcium-alkaline volcanic rocks such as andesite and dacite, which probably originated from intraplate collision or volcanic arc structural backgrounds related to the collision belt of the Cathaysia Block to the Yangtze Block. Productivity indicators (P content, excess Si, P/Al, Cu/Al, and Ni/Al) in the WF and LM1-3 members are all significantly higher than those in the Lingxiang (LX) and LM4-5+ members. The higher biological productivity during the Ordovician-Silurian (O–S) transition was attributed to the massive and intensive volcanism. The fertilization by volcanic ash brought abundant biologically relevant nutrient elements (N, P, Si, Fe, and Al) into the ocean, thus triggering the phytoplankton bloom and enhancing primary biological productivity. All the redox condition indexes (MoEF, UEF, NiEF, VEF, Mo/TOC, Corg /P, and U/Th) positively correlate with TOC content. During the O–S transition, the intensive and massive volcanic eruptions triggered global cooling, sea-level changes, late Ordovician mass extinction, and primary productivity increases, thus promoting anoxic, and possibly intermittently euxinic bottom conditions. In addition, the deposited bentonite layers had a strong capacity for oxygen isolation. Volcanism should be considered when modeling the OM accumulation of the WF-LM shales. Highlights: WF Formation and LM1~4 members are the bentonite beds concentrated sections. Bentonites are characterized by intermediate-acid calcium-alkaline volcanic rocks. Bentonites are correlated with the collision of Cathaysian to Yangtze Blocks. The volcanic ashes enhanced the primary biological productivity. The volcanism promoted marine anoxic-euxinic bottom conditions.